REMODELING ANATOMI BAHU AKIBAT AKTIVITAS OVERHEAD: KAJIAN LITERATUR PADA ATLET SEPAK BOLA, RENANG, DAN VOLI - Nadia Purnama Dewi; Melya Susanti; Yuliza Birman; Ade Teti Vani (Nusantara Hasana Journal, 2025)
Repetitive and intense overhead activities, such as those found in swimming, volleyball, and goalkeeping in football, cause repetitive biomechanical stress on the shoulder joints. This exposure has the potential to cause anatomical remodelling, in the form of significant structural and functional adaptations in the shoulder complex, including the scapula, humerus, and supporting soft tissues. This study analyses narrative literature on research from the past five years regarding anatomical changes caused by overhead activities in swimmers, volleyball players, and footballers. The Scopus, PubMed, and DOAJ databases were used to search for literature focusing on shoulder structural changes and biomechanics. Articles must be in English or Indonesian and open-access. A literature synthesis revealed that the shoulders of overhead athletes undergo anatomical changes, including increased lateral rotation, decreased medial rotation, and increased scapular asymmetry. Anatomical applications also vary across specific sports. Volleyball athletes have larger rotator cuff muscles and a higher risk of subacromial impingement. In contrast, swimmers have a higher risk of humeral epiphysiolysis due to the frequent shoulder movements they experience from a young age. In football goalkeepers, remodelling is more focused on shoulder muscle imbalance and reduced glenohumeral stability due to direct contact and ball-reaching activities. Overhead activities in sports cause unique structural adaptations in the shoulder, depending on the type of sport and specific movement patterns. A deep understanding of this remodelling is crucial for designing targeted injury prevention and rehabilitation programmes for overhead athletes.